Rational Design and Synthesis of Naphthalene Diimide Linked Bis-Naphthalimides as DNA Interactive Agents - Malik, M. Shaheer; Farooq Adil, Syed; Moussa, Ziad; Altass, Hatem M.; Althagafi, Ismail I.; Morad, Moataz; Ansari, Mohammad Azam; Sajid Jamal, Qazi Mohammad; Obaid, Rami J.; Al-Warthan, Abdulrahman A.; Shaik, Thokhir B.; Ahmed, Saleh A. (Frontiers in Chemistry, 2021)
A molecular modelling assisted rational design and synthesis of naphthalene diimide linked bisnaphthalimides as potential DNA interactive agents is described. Chemical templates incorporating naphthalene diimide as a linker in bisnaphthalimide motif were subjected to molecular docking analysis at specific intercalation and telomeric DNA G-quadruplex sites. Excellent results were obtained, which were better than the standards. A short and convenient synthetic route was employed to access these hybrids experimentally, followed by evaluation of their ability to cause thermal denaturation of DNA and cytotoxic properties along with ADME predictions. The obtained results provided useful insights and two potential molecules were identified for further development.